Fabrication and Experimental Performance Analysis of a Parabolic Solar Dish Collector - Ali Jasim; Zahraa Ali Abd-Alsattar Hassn (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study aims to design and experimentally evaluate the performance of a parabolic dish solar collector for water heating and evaporation. The primary objective is to measure the system's efficiency and explore ways to optimize solar energy utilization. Methodology: A 180 cm parabolic dish covered with aluminum and a copper tube absorber was fabricated. Inlet and outlet water temperatures, solar irradiance, mass flow rate, and thermal efficiency were measured on April 16–17, 2023. Results: The collector reached a peak efficiency of 76.5% at 12:30 PM, with solar irradiance of 956 W/m². Efficiency declined in the afternoon as solar irradiance decreased, showing a strong relationship between performance and solar radiation. Conclusions: The parabolic dish collector is effective for water heating and evaporation. Its performance can be improved by expanding the exposure area, using more reflective materials, applying anti-scattering coatings, and adding an electronic sun-tracking system. Limitations: The study is limited to a single dish size and specific climatic conditions. Manual measurements were conducted only during daytime, without accounting for seasonal variations or extreme weather conditions. Contribution: This research provides empirical evidence on parabolic dish collector performance and practical recommendations for improving solar thermal efficiency.